Microbial diversity and fermentation optimization of tempoyak from Durian and Durian Lai - MARWATI MARWATI; KRISHNA PURNAWAN CANDRA; ASWITA EMMAWATI; MIFTAKHUR ROHMAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Marwati, Candra KP, Emmawati A, Rohmah M. 2025. Microbial diversity and fermentation optimization of tempoyak from Durian and Durian Lai. Biodiversitas 26: 4908-4922. Tempoyak, a traditional fermented durian product, is a rich source of probiotic lactic acid bacteria (LAB) with potential as a functional food. This study aimed to optimize the fermentation conditions of tempoyak made from Durian Lai (Durio zibethinus × Durio kutejensis, DZ_K) using Response Surface Methodology-Box Behnken Design (RSM-BBD) and to compare its bacterial community structure with that of regular durian tempoyak (DZ). The effects of salt (2-4%), sugar (0.5-1.5%), and fermentation time (2-4 days) on LAB counts, pH, acidity, sugar, and moisture content were evaluated, and optimal conditions for DZ_K were identified as 2.46% salt, 1.01% sugar, and 2 days of fermentation, yielding log 9.5 CFU/g LAB, pH 5.56, and acceptable acidity and sugar levels. Microbial profiling using 16S rRNA gene sequencing (Illumina MiSeq) revealed distinct bacterial communities, with DZ_K dominated by Pediococcus (56.5%) and Weissella (12.23%), while DZ exhibited greater diversity, including Leuconostoc (42.43%) and Acetobacter (8.78%). Alpha diversity indices indicated higher microbial richness in DZ, and ordination analyses confirmed a clear separation between the two fermentation types. These findings suggest that DZ fermentation supports broader microbial diversity, potentially enhancing flavor complexity and fermentation stability, whereas DZ_K fermentation favors a LAB-driven process, improving product stability and probiotic potential, thereby providing a scientific basis for optimizing tempoyak production to enhance microbiological quality and safety.